Pengaruh Sistem Pengendalian Internal Terhadap Siklus Produksi Barang Jadi Pada CV Zefanya Busana Mandiri - Imannuela Kristina Agustien; Hermawan Triono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the influence of the internal control system on the production cycle of finished goods at CV Zefanya Busana Mandiri, specifically operating in the clothing production section. This study focuses on the implementation of the five main components of internal control based on the COSO framework, namely control environment, risk assessment, control activities, information and communication, and monitoring. The type of research used is quantitative research using a questionnaire. The sampling process was conducted using purposive sampling method. The population that is the object of the research is all employees directly involved in the production process, totaling 40 employees. The analysis method applied is multiple linear regression. The result of the data analysis show that partially, only the control environment, and supervision have a significant positive impact on the production cycle, while risk assessment and control activities do not show a significant effect on the production cycle. The coefficient of determination obtained is 0,767 or 76,7% of the production cycle is influenced by the control environment, risk assessment, control activities, information and communication, and monitoring, while the remaining 23,3% of other variations is influenced by other variables not included in this study.